Daily precipitation in Northern Iberia: Understanding the recent changes after the circulation variability in the North Atlantic sector. Issue 19 (6th October 2015) - Sáez de Cámara, E.; Gangoiti, G.; Alonso, L.; Iza, J.
Abstract Trends in the characteristics of daily precipitation over Northern Iberia (NIB) are analyzed after 14 daily records covering the last 40 years plus seven century‐length time series. Results reveal an evolution to drier conditions with subregional variations: in western and central subregions, the decrease in both the occurrence and the intensity of wet days results in a statistically significant decline of total precipitation. Contrary to other regions in the Iberian Peninsula, the lack of correlation between the North Atlantic Oscillation (NAO) index and the observed rainfall anomalies within NIB suggests that the dominance of a positive NAO mode from the late 1970s to 2002 cannot explain the trends. The land‐sea and mountain distribution creates sharp rainfall transitions depending on the pathways of the moisture‐laden winds. Consequently, NIB and other mountainous regions in the margins of the European continental water divide are sensitive to small changes in the NAO pressure centers and can exhibit both positive and negative rainfall anomalies for each NAO mode. A novel methodology for identifying changes in the NAO modes, consistent with the observed pressure/precipitation anomalies at both continental and regional scales, is presented. After the disaggregation of each dominant NAO wet season into two categories, the main rainfall changes in the NIB region can be explained in the context of the NAO variability during the last decades. The reported (sub)regional rainfall differences stress the need of caution when using NAO reconstructions, based in site specific rainfall anomalies, for the interpretation of the past climate precipitation variability in areas of complex terrain.